Perancangan Sistem Informasi Geografis Perlengkapan Jalan Berbasis Daerah Rawan Kecelakaan - Handayani, Sabrina; Angga, Dessy; Pasa, Panji (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2022)
Accidents often occur with several influencing factors and often repeat at a point which is often referred to as an accident-prone area. Accident-prone areas must be supported by the design of a road equipment geographic information system to make it easier to find out road equipment around the place. Balangan Regency is one of the areas in the province of South Kalimantan, it is in a strategic position because it is a crossing route between regions and the route to the province of East Kalimantan. To improve service to existing traffic, one of the efforts made is to improve the quality of road equipment. The problems that occur in the data and management system at the Balangan Regency Transportation Office can now be said to be bad and not up to date. In addition, there are many roads that are not equipped with signs and in accident-prone areas do not have adequate road equipment. The purpose of this study is to analyze the need for signs on roads in Balangan Regency and the needs for road equipment in accident-prone areas. The results of the analysis are displayed using the Geographic Information System method in the ArcGIS 10.3 application, the results of which are to facilitate the Department of Transportation in carrying out maintenance and decision making in planning road equipment as an effort to improve transportation services and safety in Balangan Regency.